pharmaceutical-sciences 2020
DOI: 10.36468/pharmaceutical-sciences.657
|View full text |Cite
|
Sign up to set email alerts
|

Oleanolic Acid Induces Apoptosis and Necrosis in Lo2 Cells

Abstract: Xiao et al.: Oleanolic acid-induced cell death This study mainly focused on the evaluation of cytotoxicity of oleanolic acid on normal human hepatic cells. Normal human hepatic cells were exposed to different concentrations of oleanolic acid and the results demonstrated that oleanolic acid induced cell death in a concentration-and time-dependent manner in LO2 cells. Low concentration of oleanolic acid (40 μM) induced apoptosis. Cleavage of caspase 3/7/9 and decrease of mitochondrial membrane potential was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…After 72 h, highest percentage of necrotic cells could be seen in the treatment of higher concentrations of both compounds. This outcome is similar to those reported in other forms of cell lines [ 25 , 26 ], suggesting that cells that are not acutely damaged may activate a programmed suicide mechanism while acute cytotoxicity may cause necrosis.…”
Section: Discussionsupporting
confidence: 87%
“…After 72 h, highest percentage of necrotic cells could be seen in the treatment of higher concentrations of both compounds. This outcome is similar to those reported in other forms of cell lines [ 25 , 26 ], suggesting that cells that are not acutely damaged may activate a programmed suicide mechanism while acute cytotoxicity may cause necrosis.…”
Section: Discussionsupporting
confidence: 87%
“…However, clinical use of OA‐containing herbal medicines can cause cholestatic liver injury (Milkiewicz & Heathcote, 2011). Studies have found that high concentrations of OA can cause cytotoxic effects (Tuncay et al, 2018; Xiao et al, 2020), while in animal experimental studies show that OA can cause cholestatic liver injury (Liu, 2005; Sato et al, 2007).…”
Section: Introductionmentioning
confidence: 99%